2021
DOI: 10.3390/cells10102799
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Induced by Sound Stimulation Enhances Anthocyanin Accumulation in Grape Berry Skin through Direct Upregulation of UDP-Glucose: Flavonoid 3-O-Glucosyltransferase

Abstract: Global warming has resulted in the loss of anthocyanin accumulation in berry skin. Sound stimulation can be used as a potential method for enhancing fruit color development since many plants recognize sound vibration as an external stimulus and alter their physiological status in response to it. Sound stimulation (sine wave sound at 1000 Hz) enhanced anthocyanin accumulation in grape cultured cells and berry skins in field-grown grapevines at the early stage of ripening. The transcription of UFGT and ACO2, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…Combined transcriptome and metabolome analyses revealed that sucrose-6-phosphatase, alpha, alph-trehalase, and beta fructofuranosidase genes jointly regulate the accumulation of sucrose and trehalose during “Zuoshan No.1” development. The DEGs during S1-S4 comprises the ripening-related protein-like gene and chalcone synthase gene, which is the first enzyme activated the flavonoid biosynthetic pathway (Waki et al ., 2020), UDP-glucose: flavonoid 3-O-glucosyltransferase gene, which promotes anthocyanin accumulation in grape (Yamazaki et al ., 2021), SWEET gene, which is a sugar transporter and uniporter gene (Chong et al ., 2014), ethylene-responsive transcription factor 3-like gene, certaining bHLH, MYB transcription factor genes, and WD repeat-containing protein genes. Most of these genes may be involved in Va berry ripening.…”
Section: Discussionmentioning
confidence: 99%
“…Combined transcriptome and metabolome analyses revealed that sucrose-6-phosphatase, alpha, alph-trehalase, and beta fructofuranosidase genes jointly regulate the accumulation of sucrose and trehalose during “Zuoshan No.1” development. The DEGs during S1-S4 comprises the ripening-related protein-like gene and chalcone synthase gene, which is the first enzyme activated the flavonoid biosynthetic pathway (Waki et al ., 2020), UDP-glucose: flavonoid 3-O-glucosyltransferase gene, which promotes anthocyanin accumulation in grape (Yamazaki et al ., 2021), SWEET gene, which is a sugar transporter and uniporter gene (Chong et al ., 2014), ethylene-responsive transcription factor 3-like gene, certaining bHLH, MYB transcription factor genes, and WD repeat-containing protein genes. Most of these genes may be involved in Va berry ripening.…”
Section: Discussionmentioning
confidence: 99%
“…For the past several decades, the average temperatures in wine-grape-producing regions around the world have continued to increase, culminating in loss of berry quality including anthocyanin content in grape berry skin [39,40]. To promote anthocyanin accumulation in grape berry skin under future climate conditions, many researchers have explored specific viticultural practices [7][8][9]11] and chemical applications [13,15,16,[41][42][43]. Interestingly, the simultaneous increase of anthocyanin and geraniol contents in grape berries subjected to viticultural practices or chemical application was occasionally observed.…”
Section: Discussionmentioning
confidence: 99%
“…Viticultural practices, including trunk girdling [7], leaf removal [8], and cluster thinning [9], have been developed to mitigate the effects of global warming on grape berry skin coloration [10]. It was recently reported that sound stimulation (sine wave sound Plants 2022, 11, 1694 2 of 13 at 1000 Hz) enhanced anthocyanin accumulation in grape berry skins of field-grown grapevines at the early stage of ripening [11]. However, these cultivation techniques are expensive and require expertise and a heavy workload.…”
Section: Introductionmentioning
confidence: 99%
“…Plant anthocyanin biosynthesis is regulated by many factors, such as temperature, hormonse, microRNAs, and epigenetics (Zhang et al, 2012;Yamazaki et al, 2021). To understand the regulation of potato anthocyanin biosynthesis, research has primarily focused on analysis of key gene functions and regulation mechanisms, particularly of structural genes, including F3'5'H, DFR, ANS, and 3GT (Jung et al, 2005;Wei et al, 2012;Zhang et al, 2020), and MBW transcription factors (Li et al, 2014;Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%